2011
DOI: 10.1166/jnn.2011.4356
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zn<SUP>2+</SUP> Source Concentration on Hydrothermally Grown ZnO Nanorods

Abstract: We studied the effect of Zn2+ source concentration on the structural and optical properties of hydrothermally grown ZnO nanorods. The nanorods were grown on ZnO/p-Si(111) substrate using by a hydrothermal process in various concentrations of reagent at a low temperature (approximately 95 degrees C) and the structural and optical characteristics of ZnO nanorods were subsequently investigated by X-ray diffraction, field-emission scanning electron microscopy, and room temperature photoluminescence. The results de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…It is evident that there is a slight lattice deformation in the Cu-ZnO lattice, which may be assigned to the diminishing Cu Zn -O bonds [32]. In this study, with up to 2% Cu concentration from the two precursors, neither the Cu nor CuO phases are observed in the XRD measurements, which indicates that the Cu impurities are dissolved completely in the ZnO crystal lattice [26,30]. …”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…It is evident that there is a slight lattice deformation in the Cu-ZnO lattice, which may be assigned to the diminishing Cu Zn -O bonds [32]. In this study, with up to 2% Cu concentration from the two precursors, neither the Cu nor CuO phases are observed in the XRD measurements, which indicates that the Cu impurities are dissolved completely in the ZnO crystal lattice [26,30]. …”
Section: Resultsmentioning
confidence: 83%
“…This shift is more significant for sample S3. On the other hand, previous research showed that at low concentrations (<1.5 at.%) of Cu, the peak position is not significantly affected by Cu doping, while at high concentration, a slight shift towards higher angles is reported due to the substitution of Zn 2+ (ionic radii = 0.074 nm) by Cu 2+ (ionic radii = 0.057 nm) [30,31]. Additionally, these changes in crystallinity might be due to the changes in the atomic environment as a result of Cu incorporation into the ZnO lattice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a continuous increase in the solution concentration may not increase the density of the nanowires when its density is larger than the saturation density. Kim et al [84] reported that the density and diameter of ZnO nanorods are especially sensitive to the concentration of the reactants. Furthermore, the structural transition is shown by increasing the concentration.…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%
“…Tailoring the morphology, shape, and size of ZnO could be a way of expanding its potential especially in solar cell and sensor technologies where reaction at the surface is very crucial. Works have been reported for controlling size and shape of ZnO nanostructures like varying the initial zinc and hydroxyl ion concentrations [5,6] and also by introducing silica (SiO 2 ) to ZnO as a concept of composite material [7,8]. With good mechanical resistance and high dielectric strength, SiO 2 is likely to be an ideal component to enhance the properties of ZnO.…”
Section: Introductionmentioning
confidence: 99%